IMPLEMENTASI PRODUK TABUNGAN EASY WADIAH DAN EASY MUDHARABAH DALAM PRAKTIK PELAYANAN DI BANK SYARIAH INDONESIA - Rosalia Indah Ariani (Jurnal Ilmiah Akuntansi, 2026)
Islamic banking plays a strategic role in providing financial services in accordance with Islamic principles. Bank Syariah Indonesia (BSI), as the largest Islamic bank in Indonesia, offers various savings products, including Easy Wadiah Savings and Easy Mudharabah Savings. This study aims to analyze the implementation of these two savings products in Islamic banking service practices at Bank Syariah Indonesia, Tegal Sutoyo Sub-Branch Office. This research employs a qualitative descriptive approach with data collection techniques consisting of direct observation during the Field Work Practice (PPL) and literature study of Islamic banking references and DSN-MUI fatwas. The results indicate that the implementation of Easy Wadiah and Easy Mudharabah Savings at BSI KCP Tegal Sutoyo is in accordance with Islamic principles and DSN-MUI regulations. Easy Wadiah Savings are more favored by customers due to transaction flexibility and the absence of monthly administrative fees, while Easy Mudharabah Savings require a deeper understanding of the profit-sharing mechanism. The study concludes that both Islamic savings products have been properly implemented, however, continuous customer education regarding contract differences and profit-sharing systems is necessary.